Bone tissue engineering using polyetherketoneketone scaffolds combined with autologous mesenchymal stem cells in a sheep calvarial defect model. Issue 8 (August 2016) - Adamzyk, Carina; Kachel, Paul; Hoss, Mareike; Gremse, Felix; Modabber, Ali; Hölzle, Frank; Tolba, Rene; Neuss, Sabine; Lethaus, Bernd
Abstract: Polyetherketoneketone (PEKK) a high performance thermoplastic polymer that is FDA-approved for cranio- and maxillo-facial as well as spineal surgery. We studied the viability, growth and osteogenic differentiation of bone marrow-derived human and sheep mesenchymal stem cells (MSC) in combination with a 3D scaffold made of PEKK using different cell-based assays. To investigate if autologous MSC, either undifferentiated or osteogenically pre-differentiated, augmented bone formation after implantation, we implanted cell-seeded 3D PEKK scaffolds into calvarial defects in sheep for 12 weeks. The volume and quality of newly formed bone were investigated using micro-computer tomography (micro-CT) and histological stainings. Our results show that the 3D PEKK scaffolds were cyto- and bio-compatible. They allowed for adherence, growth and osteogenic differentiation of human and ovine MSC. However, bone healing seemed unaffected by whether the scaffolds were seeded with MSC. Considerable amounts of newly formed bone were found in all PEKK treated groups, but a fibrous capsule was formed around the implants regardless of cell seeding with MSC.